2020
DOI: 10.1101/2020.12.04.20244327
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Covid-19 Related Immunization Disruptions in Rajasthan, India: A Retrospective Observational Study

Abstract: IntroductionGovernments around the world suspended immunization outreach to control COVID-19 spread. Many have since resumed services with an emphasis on catch-up vaccinations to reach children with missed vaccinations. This paper evaluated immunization disruptions during India’s March-May 2020 lockdown and the extent to which subsequent catch-up efforts reversed them in Rajasthan, India.MethodsIn this retrospective observational study, we conducted phone surveys to collect immunization details for 2,144 child… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…Another set of data coming from Rajasthan, India reported significant lapses in the timeliness of administration of RI doses. [ 9 ] Subgroup analysis found that children in less educated and poorer households already had lower pre-COVID levels of immunization and were subject to greater declines in RI coverage during and after lockdown. The authors analyzed government’s administrative data obtained from HMIS and commented that increase in post-lockdown numbers may not reflect an increased RI coverage but may be due to seasonal fluctuations or migration of people.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Another set of data coming from Rajasthan, India reported significant lapses in the timeliness of administration of RI doses. [ 9 ] Subgroup analysis found that children in less educated and poorer households already had lower pre-COVID levels of immunization and were subject to greater declines in RI coverage during and after lockdown. The authors analyzed government’s administrative data obtained from HMIS and commented that increase in post-lockdown numbers may not reflect an increased RI coverage but may be due to seasonal fluctuations or migration of people.…”
Section: Findings and Discussionmentioning
confidence: 99%
“… Abdel-Kader and Unruh, 2009 , Dupas and Jain, 2020 , IndiaSpend, 2020a , Jain and Chopra, 2021 , Sever et al, 2015 , Thayer et al, 2021 , The Guardian, 2021 , The Lancet COVID-19 Commission India Task Force, 2021…”
Section: Uncited Referencesmentioning
confidence: 99%
“…This is alarming and may have contributed to the recently reported increase in “Wild virus type 1” confirmed polio cases [ 74 ]. In India, data from Rajasthan province (where lockdown restrictions were greatest between March and May 2020) indicates an 87% relative decline in the number of fully immunized infants aged 9–11 months in April 2020 compared with pre-lockdown levels, although this was then somewhat compensated by the relative 23% increase in May 2020 [ 75 ]. However, while nationwide data shows a similar decline (69% in April 2020), there was no discernible recovery, with rates remaining lower in May and June 2020 (by 23% and 31% respectively) [ 75 ].…”
Section: Disruption To Routine Immunization Servicesmentioning
confidence: 99%
“…In India, data from Rajasthan province (where lockdown restrictions were greatest between March and May 2020) indicates an 87% relative decline in the number of fully immunized infants aged 9–11 months in April 2020 compared with pre-lockdown levels, although this was then somewhat compensated by the relative 23% increase in May 2020 [ 75 ]. However, while nationwide data shows a similar decline (69% in April 2020), there was no discernible recovery, with rates remaining lower in May and June 2020 (by 23% and 31% respectively) [ 75 ]. It remains to be seen how the more recent devastating upsurge in the COVID-19 pandemic in India has impacted on current immunization patterns.…”
Section: Disruption To Routine Immunization Servicesmentioning
confidence: 99%